High-throughput and ultra-sensitive single-cell profiling of multiple microRNAs and identification of human cancer. Issue 70 (12th August 2019) - Li, Lu; Lu, Meng; Fan, Yuanyuan; Shui, Lingling; Xie, Shuting; Sheng, Renjie; Si, Haibin; Li, Qingling; Wang, Yiguo; Tang, Bo
Abstract : We established an efficient method for single-cell multiple miRNA analysis by droplet microfluidics with high sensitivity and high throughput. Abstract : We established an efficient method for single-cell miRNA analysis by droplet microfluidics, which has high sensitivity of single molecule detection and high throughput. Single-cell analysis of multiple miRNAs in various cells shows that miRNA expression is closely related to cancer type. CTC analysis shows that the method is applicable for rare cell analysis.